Saxitoxin Poisoning in Green Turtles (Chelonia mydas) Linked to Scavenging on Mass Mortality of Caribbean Sharpnose Puffer Fish (Canthigaster rostrata-Tetraodontidae) - Barrientos, Rocío González; Hernández-Mora, Gabriela; Alegre, Fernando; Field, Theresa; Flewelling, Leanne; McGrath, Sara; Deeds, Jonathan; Chacón, Yajaira Salazar; Rojas Arrieta, Karla; Vargas, Emilia Calvo; Artavia, Karen Berrocal; Stacy, Brian A. (Frontiers in Veterinary Science, 2019)
Fish within the family Tetraodontidae are potential sources of both endogenous tetrodotoxins (TTXs) and dietary derived saxitoxins (STXs). Ingestion of fish tissues containing these toxins by other vertebrates can lead to severe illness and death. The Caribbean sharpnose puffer (Canthigaster rostrata) is a widespread tetraodontid species within the western Atlantic. Mass settlement of juveniles into foraging habitats have been associated with large-scale puffer fish mortality events. In 2013, 2014, and 2017, puffer mortality events on the southern Caribbean coast of Costa Rica were also associated with strandings of green turtles (Chelonia mydas) found to have fed on C. rostrata. Stranded sea turtles were found dead without apparent cause or alive with severe neurological signs that resolved during short periods of captivity. Puffer fish and turtle organ samples were analyzed for both TTXs and STXs. Concentrations of TTXs were extremely low in the fish (0.5–0.7 μg/g) and undetectable in turtle stomach contents. However, concentrations of STXs in whole fish (16.6–47.5 μg STX-eq/g) exceeded the 0.8 μg STX-eq/g human seafood safety threshold for STXs by orders of magnitude. Saxitoxins were also detected in samples of stomach contents (ingested fish), brain, lung, kidney, and serum from three affected turtles. Study results indicate that saxitoxicosis resulting from opportunistic foraging on C. rostrata during fish mortality events may be a significant factor in episodic stranding of green sea turtles in this region.